Pengaruh Promosi terhadap Tingkat Pendapatan Toko Pakaian Pasar Baru Kecamatan Panyabungan Kabupaten Mandailing Natal - Putri Yani; Ade Khadijatul Z Hrp; Vebri Sugiharto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of promotions on the income of clothing businesses in Pasar Baru Panyabungan, Mandailing Natal Regency, North Sumatra. Data collection was carried out through a survey of 56 respondents consisting of market traders, where 35.71% of the respondents were men and 64.29% were women. The majority of respondents were aged between 26-40 years (35.71) and had a high school education or equivalent (62.50%). The results of simple linear regression analysis show that promotion has a significant influence on income, with a regression coefficient of 0.484. This means that every one unit increase in the promotion variable has the potential to increase revenue by 0.484 units. The regression model obtained is Y= 82.586 + 0.484 The validity test shows that all statement items are valid with a calculated r value greater than r table (0.2221), while the reliability test with Cronbach alpha shows a value of 0.685 for promotion and 0.839 for income, which means the instrument used is reliable. In addition, the classical assumption test ensures that the data is normally distributed and there is no heteroscedasticity. The research also identifies challenges such as intense competition and environmental issues in the market. These findings emphasize the importance of effective promotional strategies, supported by government policies that encourage sustainable economic growth in traditional markets.